Responder analysis for pain relief and numbers needed to treat in a meta-analysis of etoricoxib osteoarthritis trials: bridging a gap between clinical trials and clinical practice - Moore, R; Moore, O; Derry, S; Peloso, P; Gammaitoni, A; Wang, H (BMJ Publishing Group, 2010)
Background: Population mean changes from clinical trials are difficult to apply to individuals in clinical practice. Responder analysis may be better, but need validating for levels of response and treatment duration. Methods: The numbers of patients with pain relief over baseline (≥15%, ≥30%, ≥50%, ≥70%) at 2, 4, 8 and 12 weeks of treatment were obtained using the WOMAC 100 mm visual analogue pain subscale score for each treatment group in seven randomised placebo-controlled trials of etoricoxib in osteoarthritis lasting ≥6 weeks. Dropouts were assigned 0% improvement from baseline from then on. The numbers needed to treat (NNTs) were calculated at each level of response and time point. Results: 3554 patients were treated with placebo, etoricoxib 30 mg and 60 mg, celecoxib 200 mg, naproxen 1000 mg or ibuprofen 2400 mg daily. Response rates fell with increasing pain relief: 60-80% experienced minimally important pain relief (≥15%), 50-60% moderate pain relief (≥30%), 40-50% substantial pain relief (≥50%) and 20-30% extensive pain relief (≥70%). NNTs for etoricoxib, celecoxib and naproxen were stable over 2-12 weeks. Ibuprofen showed lessening of effectiveness with time. Conclusion: Responder rates and NNTs are reproducible for different levels of response over 12 weeks and have relevance for clinical practice at the individual patient level. An average 10 mm improvement in pain equates to almost one in two patients having substantial benefit.